SINGULAR METHOD OF INCREASE OF EXTENT OF COMPRESSION OF INTERNAL COMBUSTION ENGINES - N. K. Sanaev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In work, for the purpose of increase of extent of compression in the cylinder of the internal combustion engines (ICE) it is offered to use the modified piston and the device for determination of frequency of the vibration formed by working process in the combustion chamber.